2008
DOI: 10.1091/mbc.e07-07-0682
|View full text |Cite
|
Sign up to set email alerts
|

S100A11, an Dual Mediator for Growth Regulation of Human Keratinocytes

Abstract: We previously revealed a novel signal pathway involving S100A11 for inhibition of the growth of normal human keratinocytes (NHK) caused by high Ca ؉؉ or transforming growth factor ␤. Exposure to either agent resulted in transfer of S100A11 to nuclei, where it induced p21 WAF1 . In contrast, S100A11 has been shown to be overexpressed in many human cancers. To address this apparent discrepancy, we analyzed possible new functions of S100A11, and we provide herein evidence that 1) S100A11 is actively secreted by N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(104 citation statements)
references
References 58 publications
5
95
0
Order By: Relevance
“…The biological relevance of ANXA1 being constitutively cleaved in such cancer cells and having no capacity to bind S100A11 as shown in this study is not clear. One possible interpretation comes from our recent findings that S100A11 was secreted from NHK on exposure to EGF and that exogenous S100A11 induced EGF in turn, thus maintaining cell growth in a positive feedback manner (31).…”
Section: Discussionmentioning
confidence: 99%
“…The biological relevance of ANXA1 being constitutively cleaved in such cancer cells and having no capacity to bind S100A11 as shown in this study is not clear. One possible interpretation comes from our recent findings that S100A11 was secreted from NHK on exposure to EGF and that exogenous S100A11 induced EGF in turn, thus maintaining cell growth in a positive feedback manner (31).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown to inhibit other kinases with much higher IC 50 values (Brehmer et al, 2005). As an alternative, we therefore treated cells with neutralizing anti-EGF antibody, which specifically inhibits EGF-dependent cell proliferation (Sakaguchi et al, 2008), and found that this treatment abolished PH-Akt-GFP recruitment to force-loaded E-cadherin receptors on MCF7 cells ( Fig. 5F; n>40, two experiments).…”
Section: Force-loading E-cadherin Activates Pi3k Upstream Of Integrinsmentioning
confidence: 99%
“…Gefitinib is an EGFR-specific, non-competitive inhibitor that blocks EGFR kinase activity (Brehmer et al, 2005;Paez et al, 2004). EGF was neutralized with 5 µg/ml human monoclonal anti-EGF antibody (R&D Systems, Minneapolis, MN: Mouse IgG1 Clone #10825) for 30 min (Sakaguchi et al, 2008). When blocking EGF during MTC measurements, cells were bathed in medium containing anti-EGF antibody.…”
Section: Cell Lines Protein Production and Inhibitorsmentioning
confidence: 99%
“…S100A11 binds to p53 and to the DNA repair protein Rad54B as well (FernandezFernandez, Rutherford, and Fersht 2008;Murzik et al 2008). S100A11 has also been found to interact with RAGE and to trigger RAGE dependent intracellular signaling in osteoarthritis (OA) and in human keratinocytes (Cecil et al 2005;Sakaguchi et al 2008). …”
Section: S100a6mentioning
confidence: 99%